Helminth parasites of some birds in Newfoundland - Threlfall, William (Canadian Journal of Zoology, 1968)
One hundred and thirty-two birds of 33 species were examined for helminth parasites in Newfoundland, Canada, during the period December, 1965, to March, 1968. A total of 27 species of helminths were identified, including five new host records. Five species of trematodes, 13 of cestodes, 7 of nematodes, and 2 of acanthocephala were recovered. The food found in the stomachs of the birds examined was also recorded.